End of Project: RIGS16-350-0514 - Htike@Muhammad Yusof, Zaw Zaw (2017)
This project proposes a novel machine learning algorithm called deep auto encoder network for learning the glass break model in a semi-supervised manner from audio data and for accurate detection of glass break sounds using unordered fuzzy rule induction algorithm.